2017
DOI: 10.5547/01956574.38.1.jyou
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Effects of Nonlinear Electricity Pricing

Abstract: Block pricing is widespread among electricity and water utilities to protect lowincome households and to encourage energy conservation through higher marginal prices. However, whether a block pricing system achieves those objectives is controversial. In this article, we analyze the impact of alternative electricity pricing systems on the welfare of consumers for the case of residential electricity block pricing in Korea. To do this, we first develop a theoretical model to compute each household's welfare chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Additional research comparing healthy people to patients with COPD has also demonstrated a lower standard of life related to health among those suffering from impaired lung function 9 ) . In addition, social and economic expenses caused by COPD are forecasted to rise steadily 10 ) , demonstrating the need to take additional measures to improve lung function.…”
Section: Introductionmentioning
confidence: 99%
“…Additional research comparing healthy people to patients with COPD has also demonstrated a lower standard of life related to health among those suffering from impaired lung function 9 ) . In addition, social and economic expenses caused by COPD are forecasted to rise steadily 10 ) , demonstrating the need to take additional measures to improve lung function.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we want to perform statistical inference regarding the Equivalent Variation. This application is interesting in itself because electricity services represent a significant share of households' budgets, 1 and this fact is prominent for the poor population (Gomez-Lobo, 1996, You andLim, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…within an endogenous framework to analyze these welfare implications. From a microeconomic perspective, there are three main streams: consumer surplus (Acton andMitchell, 1983, Bowitz et al, 2000), compensating variation (Gomez-Lobo, 1996, Dodonov et al, 2004 and equivalent variation (Dodonov et al, 2004, Lundgren, 2009, Ruijs, 2009, You and Lim, 2013, all of them have been estimated using frequentist approaches without consideration of uncertainty due to parameter estimates. From a theoretical standpoint, the main consideration for adopting the Bayesian approach is that it allows us to establish a statistical framework that simultaneously unifies decision theory, statistical inference, and probability theory under a single philosophically and mathematically consistent structure.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, we find that few authors have studied welfare effects due to changes within block price systems, and even fewer have introduced spatial random effects within an endogenous framework to analyze these welfare implications. From a microeconomic perspective, there are three main streams: consumer surplus (Acton andMitchell, 1983, Bowitz et al, 2000), compensating variation (Gomez-Lobo, 1996, Dodonov et al, 2004 and equivalent variation (Dodonov et al, 2004, Lundgren, 2009, Ruijs, 2009, You and Lim, 2013, all of them have been estimated using frequentist approaches without consideration of uncertainty due to parameter estimates. From a theoretical standpoint, the main consideration for adopting the Bayesian approach is that it allows us to establish a statistical framework that simultaneously unifies decision theory, statistical inference, and probability theory under a single philosophically and mathematically consistent structure.…”
Section: Introductionmentioning
confidence: 99%